2020
DOI: 10.3389/fsufs.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Conservation Agriculture to Conserve Soil Organic Carbon and the Subsequent Impact on Soil Physical, Chemical, and Biological Properties and Yield

Abstract: Increases in human populations and the emerging challenges of climate change mean that the world's agricultural systems will need to produce more food in an environment that is increasingly variable and where the quality of our natural resource base is declining. One central measure of an agricultural system's capacity to do this is its ability to preserve soil organic carbon (SOC), due to the pivotal role that this plays in maintaining soil physical, chemical, and biological properties and ultimately yield. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(133 citation statements)
references
References 198 publications
(313 reference statements)
5
94
0
1
Order By: Relevance
“…In some other conditions, such as winter crop in cold region, we did notice that not covering the soil increased the chance of yield gain compared to continuous soil cover. We showed that winter wheat in northeast of China, NT has better performance than CA, this might be because the soil cover reduced the mean soil temperature 37 , which delayed the crop establishment and growth 4,38,39 . However, it is also reported that residue cover could decrease the rate of soil temperature change 37 , increase the minimum soil temperature in extreme cold conditions [40][41][42] , and provide a buffer layer that can increase the crop resistance to the increasing climate variability and the occurrence of extreme events 4 .…”
Section: Discussionmentioning
confidence: 93%
“…In some other conditions, such as winter crop in cold region, we did notice that not covering the soil increased the chance of yield gain compared to continuous soil cover. We showed that winter wheat in northeast of China, NT has better performance than CA, this might be because the soil cover reduced the mean soil temperature 37 , which delayed the crop establishment and growth 4,38,39 . However, it is also reported that residue cover could decrease the rate of soil temperature change 37 , increase the minimum soil temperature in extreme cold conditions [40][41][42] , and provide a buffer layer that can increase the crop resistance to the increasing climate variability and the occurrence of extreme events 4 .…”
Section: Discussionmentioning
confidence: 93%
“…After seven years', the ZTFB and PNB with residues improved the OC content by 18-20% and total OC stock by 15-16% (0.0-0.10 m depth) than the CT. This would be associated with a better physical protection of particulate organic matter, greater amount of C-residues remain on the soil surface coupled with lesser turnover of macro-aggregates as well as minimal contact between residue and soil 48 . Perhaps, extensive tillage reduces OC, as it breaks open the previously protected SOM leading to the increased microbial decay 49,50 , as observed under the CT system.…”
Section: Discussionmentioning
confidence: 99%
“…We also show that there is higher chance of yield gain from CA under dryer conditions, compared to wetter environments [5][6][7]18 . This is likely due to CA improving soil aggregate stability via crop residue returns to soils, which reduces soil evaporation and surface runoff, and maintains a higher level of soil moisture content compared to CT [19][20][21][22][23][24][25][26][27] . This competitive advantage of CA comes into play for dryer climate conditions [28][29][30][31][32][33] , but does not apply in wetter and cooler environment (S2a-c, S2f-i) where the soil evaporation is less intense.…”
Section: Discussionmentioning
confidence: 99%